2022
DOI: 10.51986/ijer-2022.vol4.05
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Students’ Accommodation in Nigeria’s Tertiary Institutions

Abstract: The quality of students’ accommodation has been one of the factors that influence students’ academic performance and achievements. This has been shown in Sustainable Development Goals as related to education and housing. This paper thus assessed the quality of students’ accommodation in a Nigeria’s tertiary institution. The objectives are to determine the factors responsible for students’ choice of accommodation and examine the variation in students’ accommodation based on their quality. Multi-stage sampling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Quality housing provides the basis for social integration, stable communities, quality health and enabling milieu for students to learn (Alani, et al, 2010;Danso & Hammond, 2017, Anamali, et al, 2019. Accordingly, hostel accommodation is key to students' academic performance and achievements (Oladiran, 2013& Ajala et al, 2022; but, persistent increase in the number of students has made it difficult for Nigerian governments at all levels, to provide for the accommodation needs of students in tertiary institutions (Ajala et al, 2022). As both governments and individuals build hostel accommodations in and around tertiary institutions of Nigeria, the functionality of these facilities requires adherence to established maintenance policies and prompt response to maintenance exigencies.…”
Section: Review Of Past Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Quality housing provides the basis for social integration, stable communities, quality health and enabling milieu for students to learn (Alani, et al, 2010;Danso & Hammond, 2017, Anamali, et al, 2019. Accordingly, hostel accommodation is key to students' academic performance and achievements (Oladiran, 2013& Ajala et al, 2022; but, persistent increase in the number of students has made it difficult for Nigerian governments at all levels, to provide for the accommodation needs of students in tertiary institutions (Ajala et al, 2022). As both governments and individuals build hostel accommodations in and around tertiary institutions of Nigeria, the functionality of these facilities requires adherence to established maintenance policies and prompt response to maintenance exigencies.…”
Section: Review Of Past Literaturementioning
confidence: 99%
“…Research by Ajala et al (2022) on "quality of students' accommodation in Nigeria, case study of Federal University of Technology, Akure, (FUTA)", revealed that though students considered several factors such as security, state of the accommodation, water and power supply, freedom, proximity to classrooms, among other factors, in their choice of university hostels, yet, the most considered factors were low hostel fees and good power supply. The study further established that the off-campus accommodations had more privacy and were less congested than the on-campus hostels.…”
Section: Review Of Past Literaturementioning
confidence: 99%